Pengaruh Kualitas Pealayanan, Promosi dan Persepsi Harga Terhadap Kepuasan Pelanggan Grab Bike di Jakarta - Febria Tamaya Muliansyah; Ricky Talumantak (LPPM Universitas Asa Indonesia, 2022)
The purpose of this study was to examine the effect of service quality, promotion and price perception on Grab Bike customer satisfaction in Jakarta. Data collection using purposive sampling technique, the method used is quantitative. The sample was obtained using a questionnaire with a total of 100 respondents. Data were analyzed using multiple linear regression. The results showed that service quality, promotion, and price perception significantly affected customer satisfaction simultaneously. Partially shows that service quality, promotion and price perception have a significant efffect on costumer.